Assessment of body composition, functional capacity and pulmonary function in patients with Chronic Obstructive Pulmonary Disease - Fernanda Dultra Dias; Evelim Leal de Freitas Dantas Gomes; Roberto Stirbulov; Vera Lúcia Santos Alves; Dirceu Costa (Universidade de São Paulo, 2014)
Chronic obstructive pulmonary disease (COPD) is related to a low body mass index (BMI), reduced functional capacity and reduced bone density, thus justifying the importance of evaluating all of these parameters in the patients with the disease. This is a cross-sectional study, with sample consisting of 20 patients who performed measurement of body composition by bioelectrical impedance, evaluation of functional capacity by the distance traveled in the Incremental Shuttle Walk Test (ISWT) and assessment of severity of obstruction by spirometry. Significant differences were found between the travelled and scheduled distance in the ISWT (p<0.01), positive correlations between muscle mass and distance walked in ISWT (r=0.54 with p=0.01), with FEV1 (r=0.488 with p=0.02), FEV1 and bone mass (r=0.497 with p=0.02) and distance traveled with FEV1 (r=0,541 with p=0.01). The correlations found in this study, besides confirming the hypothesis that the severity of the obstruction presented by the change in the lung parenchyma in patients with COPD is related to changes in body composition and functional capacity reduction, also highlight the correlation with bone mass.